2022
DOI: 10.1088/1748-9326/ac5206
|View full text |Cite
|
Sign up to set email alerts
|

Limited role of soil texture in mediating natural vegetation response to rainfall anomalies

Abstract: Evidence suggests that the response of rainfed crops to dry or wet years is modulated by soil texture. This is a central tenet for certain agronomic operations in water-limited regions that rely on spatial distribution of soil texture for guiding precision agriculture. In contrast, natural vegetation in climatic equilibrium evolves to form a dynamic assemblage of traits and species adapted to local climatic conditions, primarily precipitation in water-limited regions. For undisturbed landscapes, we hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…Along the same lines, Niemeyer et al (2014) found that the relationship between woody cover and K fs along a vegetation gradient in dry tropical Nicaragua was greater for fine-textured soils than for coarser soils, which they ascribed to the impact of root-macropore formation on K fs in fine-textured soils. Our results, which differ from these observations, may partly be explained by the so-called "inverse texture effect" observed in dryland ecosystems and by which coarser soils appear to support taller and denser perennial vegetation than finer soils (Gupta et al, 2022;Noy-Meir, 1973). Such apparently contradictory observations indicate that the combined relationship of woody vegetation and soil texture on K fs is complex and requires further investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…Along the same lines, Niemeyer et al (2014) found that the relationship between woody cover and K fs along a vegetation gradient in dry tropical Nicaragua was greater for fine-textured soils than for coarser soils, which they ascribed to the impact of root-macropore formation on K fs in fine-textured soils. Our results, which differ from these observations, may partly be explained by the so-called "inverse texture effect" observed in dryland ecosystems and by which coarser soils appear to support taller and denser perennial vegetation than finer soils (Gupta et al, 2022;Noy-Meir, 1973). Such apparently contradictory observations indicate that the combined relationship of woody vegetation and soil texture on K fs is complex and requires further investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…Soils are key for maintaining the productivity of cropping systems. Their ability to retain and transport water ensures water supply during times of demand and the removal of excess water from the root zone to prevent hypoxia or anoxia (Fang and Su, 2019;Gupta et al, 2022a;Kukal et al, 2023). The water storage and transport functions of soils are determined by their hydraulic properties.…”
Section: Sammanfattningmentioning
confidence: 99%
“…These covariates are listed in Table 4. The relative importance of each covariate for explaining the variation in KL divergence was determined from the random forest analysis, and their non-linear/nonmonotonic effects were derived using partial dependencies (e.g., Gupta et al, 2022a;Jorda et al, 2015). The analysis was applied to three separate scenarios including (i) all samples, (ii) only topsoil samples (soil depth 30 cm; n = 174), and (iii) only subsoil samples (soil depth >30 cm; n = 257).…”
Section: Factors Of Soil Structure Evolution In Agricultural Soils Of...mentioning
confidence: 99%